2021
DOI: 10.21462/jeltl.v6i2.564
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Indonesian EFL Learners’ Perception of English Learning Grammar

Abstract: <em>This study presents Indonesia English as Foreign Language (EFL) learners’ perception of English learning grammar in response of ‘stigma’ appeared among learners where grammar is considered as a difficult but crucial sub-skill to master. The goals of this research are specifically to figure out whether and how grammar is seen as its disreputable status as well as to explore their competence or motivation, what obstacles that learners experience while studying it, and which learning models that learner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Both problems that prevail in Indonesia Education's curriculum synchronously relate to a statement of English grammar being difficult to learn and implement in daily conversation. That is in line with Komara and Tiarsiwi (2021) who assert that the monotonous teaching methods variation in the class going simultaneously with the teacher's imprecise explanation could develop a hindrance among the students who learn grammar.…”
Section: Ht Students and Hoteliers' Perceptions Of Grammar Rulessupporting
confidence: 83%
“…Both problems that prevail in Indonesia Education's curriculum synchronously relate to a statement of English grammar being difficult to learn and implement in daily conversation. That is in line with Komara and Tiarsiwi (2021) who assert that the monotonous teaching methods variation in the class going simultaneously with the teacher's imprecise explanation could develop a hindrance among the students who learn grammar.…”
Section: Ht Students and Hoteliers' Perceptions Of Grammar Rulessupporting
confidence: 83%
“…Due to the severe demands for the correctness in thesis writing, many students seek a convenient way to ensure their work is error-free (Nagel et al, 2020). Given that English is not the first language of Indonesian students, achieving grammatical accuracy poses a significant challenge (Komara & Tiarsiwi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The result shows that the students prefer implicit teaching strategies to facilitate the natural acquisition of the language. Komara & Tiarsiwi (2021)explored how learners perceive grammar learning. The findings of their study demonstrated that Indonesian EFL students believed that grammar was challenging yet necessary to learn and master.…”
Section: Introductionmentioning
confidence: 99%